Evaluation of bone turnover after bisphosphonate withdrawal and its influence on implant osseointegration: an in vivo study in rats - Frizzera, Fausto; Verzola, Mario Henrique Arruda [UNESP]; de Molon, Rafael Scaf [UNESP]; de Oliveira, Guilherme Jose Pimentel Lopes [UNESP]; Giro, Gabriela; Spolidorio, Luis Carlos [UNESP]; Pereira, Rosa Maria Rodrigues; Tetradis, Sotirios; Cirelli, Joni Augusto [UNESP]; Orrico, Silvana Regina Peres [UNESP] (Springer Nature, 2018)
Objectives: The aim of this study was to investigate bone turnover alterations after alendronate (ALD) withdrawal and its influence on dental implants osseointegration. Materials and methods: Seventy female Wistar rats were randomly divided in 2 groups that received on day 0 either placebo (control group—CTL; n = 10) or 1 mg/kg sodium alendronate (ALD; n = 60) once a week for 4 months. At day 120, ALD treatment was suspended for 50 animals. Then, a titanium implant was placed in the left tibia of each rat that were randomly allocated in five subgroups of ten animals each, according to the period of evaluation: day 0 (INT-0), day 7 (INT-7), day 14 (INT-14), day 28 (INT-28), and day 45 (INT-45) after ALD withdrawal. CTL group and a group that received ALD until the end of the experimental period (non-interrupted group—non-INT; n = 10) underwent implant placement on day 120. Animals were euthanized 28 days after implant surgery. Bone mineral density (BMD) of femur and lumbar vertebrae were evaluated by DXA, biochemical markers of bone turnover were analyzed by ELISA, and bone histomorphometry was performed to measure bone-to-implant contact (BIC) and bone area fraction occupancy (BAFO). Results: All groups receiving ALD showed higher BMD values when compared to CTL group, which were maintained after its withdrawal. Decreased concentrations in all bone turnover markers were observed in the non-INT group, and in the groups in which ALD was discontinued compared to the CTL group. The non-INT group showed lower %BIC and notably changes in bone quality, which was persistent after drug withdrawal. Conclusion: Collectively, the findings of this study demonstrated that ALD therapy decreased bone turnover and impaired bone quality and quantity around dental implants, and that its discontinuation did not reverse these findings. Clinical relevance: The severe suppression of bone turnover caused by the prolonged use of ALD may alter the capacity of bone tissue to integrate with the implant threads impairing the osseointegration process.
Keywords: Alendronate; Bisphosphonate; Dental implants; Osseointegration; Osteoclasts; Rats